Atypical case of lichen planus recognized by dermoscopy - Chrysoula Papageorgiou; Zoe Apalla; Elizabeth Lazaridou; Elena Sotiriou; Efstratios Vakirlis; Demetrios Ioannides; Aimilios Lallas (Mattioli1885, 2016)
Lichen planus is an inflammatory disease that affects the skin - mainly the extremities and the trunk- and the mucous membranes, the genitalia, the nails and the scalp. The diagnosis of LP is usually established clinically, based on the typical morphology and distribution of the lesions, in conjunction with the associated itch. We report a patient with LP manifesting with highly psoriasiform lesions, that could only be correctly assessed after the application of dermoscopy, which revealed LP-specific findings.